Penataan Tata Ruang Kantor Untuk Mendukung Kinerja Tenaga Administrasi Sekolah Di Sma Negeri 1 Kampar - Romenza, Lufia; Irawati, Irawati; Setyaningsih, Rini; Sabrifha, Eli (EL-EMIR Institute, 2024)
This research investigated about office spatial planning in supporting the school administrative staff performance at State Senior High School 1 Kampar. The formulations of problems in this research were to know: how office spatial planning was, what the benefits of office spatial planning were at State Senior High School 1 Kampar. The findings of this research showed that office spatial planning was properly but there were still some tables, cupboards and files that were not neatly arranged so that was a little bit disturbed. The problems found related to the use of office spatial planning at State Senior High School 1 Kampar were that there were some tables located near the entrance so that it prevented guests entering, there were some cupboards that were in which the layout was still messy, there were still arrangements of stationery and files that were not according to the place on the table of each employee, the lack of greenery in the room so it did not fell coolness sense in the room. The efforts made by schools related to the utilize of spatial planning in supporting the school administrative staff performance were working together and in arranging and organizing the office space with someone who was familiar with the room so that school administration staff felt comfortable in working and supporting the increasing administrative staff performance at the school